Formative study on slaughterhouse hygiene in Western Kenya: Summary Report - Otoigo, Lilian; Alumasa, Lorren; Majiwa, Hamilton; Hoffmann, Vivian; Ambler, Kate; Kiarie, Alice; Cook, Elizabeth A.J. (International Food Policy Research Institute, 2024)
Slaughterhouses in Western Kenya face critical challenges, including inadequate hygiene practices, poor infrastructure, insufficient water supply, and weak enforcement of regulatory standards. These deficiencies contribute to meat contamination and the transmission of zoonotic diseases such as Rift Valley Fever, brucellosis, and anthrax, as well as foodborne pathogens such as Salmonella sp. and pathogenic E.coli. Globally, foodborne illnesses result in millions of illnesses and hundreds of thousands of deaths annually, particularly among children under five. The public health and economic consequences of these risks in low and middle-income countries are significant (Havelaar et al., 2015; Jaffee et al., 2018). A qualitative study, based on interviews of key informants in the slaughter industry in Western Kenya and associated regulatory authorities, was undertaken in 2022 to document the state of slaughterhouse infrastructure and practices, explore barriers to compliance with regulatory standards, and identify practical solutions for improving conditions and enabling safer meat handling practices. This report summarizes the findings of that study and presents recommendations for interventions to improve slaughter hygiene practices.